The Phytochemical and Pharmacological Properties of Citrus sinensis ‘Maltese Half-blood’ Essential Oil Peels Extracted and Optimized by Response-surface Methodology - Kallel, Imen; Tarhouni, Nidhal; Elaguel, Asma; Mekrazi, Saoussen; Khabir, Abdelmajid; Hadrich, Bilel; Bayoudh, Ahmed (Current Pharmaceutical Biotechnology, 2023)
Background: Citrus fruits have been a valuable economic crop for thousands of years. Furthermore, citrus essential oils are significant in the perfume, food, and beverage sectors, as well as aromatherapy and medical medicines. Aims: The present study aims to evaluate the phytochemical and pharmacological potentials of the optimized Citrus sinensis ‘Maltese half-blood’ essential oils peels (CsEO) extraction yields using Response-Surface Methodology (RSM). Objective: There have been few investigations on Citrus sinensis ‘Maltese half-blood’ essential oil. Methods: Citrus sinensis ‘Maltese half-blood’ essential oil peels (CsEO) extraction yields were performed by hydro-distillation and optimized by using Response-Surface Methodology (RSM). The oils were analysed by GC-MS. Different chemical tests were used to evaluate antioxidant activities. The healing potential was evaluated using models’ wounds on Wistar rats. Results: The RSM optimization demonstrated the highest yield of CsEO of 6.89 g/100 g d.b. All three tested factors significantly influenced the CsEO extraction yield: washing saline solution concentration, washings number, and drying percentage of peels. Significant antioxidant activities were noted in CsEO: the DPPH assay reported an IC50 of 0.225 ± 0.014 mL/mg, the FRAP assay showed an IC50 of 0.235 ± 0.001, and the NO assay was an IC50 in order of 0.259 ± 0.019. CsEO was not genotoxic and considerably decreased the levels of DNA lesions induced by oxidants. Also, applying a cream with CsEO on wounds promotes significantly rapid wound healing. Conclusion: CsEO could be considered a rich natural source of antioxidants and bio-compounds to accelerate wound healing. It can be used in pharmaceutical sectors as an alternative to synthetic chemicals.
Keywords: Essential oils